Experimental investigation of quasistatic penetration tests on honeycomb sandwich panels filled with polymer foam. Issue 21 (2nd November 2020) - Hassanpour Roudbeneh, Fatemeh; Liaghat, Gholamhossein; Sabouri, Hadi; Hadavinia, Homayoun
Abstract: In this article, the quasistatic penetration tests were investigated on unfilled and polyurethane foam filled honeycomb sandwich panels. Failure mechanisms, specific energy absorption, interaction mechanisms, and some structural responses were studied. Comparing the three types of the foam filled sandwich panels with unfilled type, indicates that the absorbed energy of the first, second, and third type of the panels are 23%, 33%, and 58% more than unfilled ones, respectively. In addition, the results showed the enhancement in the dynamic strength and remarkably decrease in the damage area of the sandwich structure when its honeycomb core was filled with polymer foam.